DEVELOPMENT AND PERFORMANCE OF BASAL STEM ROT (GANODERMA) DISEASE RESISTANT COCONUT GENOTYPE IN ENDEMIC AREA - A Karthikeyan; R. Bhaskaran; M. Karthikeyan (International Coconut Community Journal, 2000)
A Tall x Tall coconut genotype resistant to basal stem rot (Ganoderma) disease has been developed for the first time in India. The resistant coconut genotype registered higher survival rate, growth characters and nut yield in disease endemic area. It contains more amount of phenolics, lignin, amino nitrogen and lesser amount of sugars which may be the factors responsible for the disease resistance.